Scheduled Castes in the Indian Labour Market Employment Discrimination and Its Impact on Poverty - Thorat, Sukhadeo K. 1949-; Madheswaran, S.; Vani, B. P. (Oxford University Press, 2023)
This study uses quantitative data analyses, empirical field research, and archival data to map the continued discrimination of Scheduled Castes in education, employment, and industry in contemporary India.
Informationen teilweise von Landing Page übernommenoder ermittelt, da Titelseite fehlt
Keywords: Dalit; Diskriminierung; Arbeitsmarkt; Indien; Dalits-India-Economic conditions; Electronic books